Model Pengembangan Agribisnis Tembakau Berkelanjutan dengan Menggunakan Metode Analytic Network Process (ANP) di Kabupaten Bojonegoro - Muafidah, Lailia; Durroh, Badiatud; Masahid, Masahid (Universitas Galuh, 2024)
Government policy to strive for the welfare of farmers, allocate the Tobacco Product Excise Revenue Sharing Fund (DBHCHT) to the form of fiscal decentralization which is distributed to tobacco-producing provinces to be used as improving the quality of raw materials, industrial development, social environment development, subsidence and assistance for seeds, seeds, fertilizers and production infrastructure as well as socialization of provisions in the excise sector to achieve sustainable agricultural development goals. The largest tobacco producing areas in Bojonegoro Regency include Kedungadem, Kepohbaru, Sugihwaras, Sumberjo and Baureno. Therefore, with this policy, it is necessary to know the strategic priorities in the development of environmentally friendly tobacco agribusiness in accordance with the concept of the dimension of sustainable agricultural development which uses five dimensions, namely ecological, economic, social, institutional and technological with the Analytic Network Process (ANP) method. The study used primary data with questionnaire tools to expert respondents, namely the Head of the Bojonegoro Food Security and Agriculture Office, 5 agricultural extension workers and heads of farmer groups and 100 tobacco farmers in Bojonegoro Regency. There are 6 sustainable agribusiness development strategies, namely improving the production and quality of tobacco organically, regular counseling, tobacco agribusiness integrating between subsystems, the existence of financial institutions for the expansion of farmer capital, expanding partnerships between tobacco farmers and the private sector and the government and finally agricultural technology assistance for farmers. The main priority of the sustainable agribusiness development strategy is to improve the production and quality of tobacco organically.